2022
DOI: 10.1063/5.0088055
|View full text |Cite
|
Sign up to set email alerts
|

Detection and evaluation of cavitation in the stator of a torque converter using pressure measurement

Abstract: Cavitation is a transient phase transition between liquid and vapor, and it often occurs in fluid machinery, especially in a hydraulic torque converter that uses oil as the working medium to transmit speed and torque. The complex and strongly coupled fluid flow in the torque converter is prone to cavitation due to high rotating speed and high-temperature working conditions. Cavitation seriously affects the working performance, transmission smoothness, and service life of the torque converter. The flow pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Guo et al measured the flow pressure in the stator of a torque converter and simulated the transient cavitation flow using computational fluid dynamics. They found that the shedding of cavitation significantly reduced hydraulic performance, hindered fluid flow, and disrupted the stability of the flow field [7]. Keisuke Tsutsumi et al from Kyushu University in Japan conducted a numerical simulation using the simplified Rayleigh-Plesset cavitation model.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al measured the flow pressure in the stator of a torque converter and simulated the transient cavitation flow using computational fluid dynamics. They found that the shedding of cavitation significantly reduced hydraulic performance, hindered fluid flow, and disrupted the stability of the flow field [7]. Keisuke Tsutsumi et al from Kyushu University in Japan conducted a numerical simulation using the simplified Rayleigh-Plesset cavitation model.…”
Section: Introductionmentioning
confidence: 99%
“…Pumps' cavitation will increase the flow leakage and pressure impact. Therefore, the discharge pressure has a strong correlation with the cavitation, in contrast to the vibration signal [31,32]. In particular, specific cavitation can damage the surface of the cylinder block and valve plate.…”
Section: Introductionmentioning
confidence: 99%